THE ROLE OF FAMILY TO ENLARGE AN INFANT’S CAPACITY IN COMMUNICATION DEVELOPMENT - Basuki Agus Suparno; Retno Hendariningrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
Linguistics and communication development in infant can best be understood by tracing the forms and patterns of interaction between a child and other family members especially his/her parents. Father and mother are significant others for a child in developing communication and linguistic capacities. From interview with and observation on families in Poh Roboh, Condong Catur, Sleman Yogyakarta-Indonesia, this research found that the position of parents in the family is important not only for making the relationship better, but also for increasing children’s preparedness for entering the society. Children’s capacities and capabilites in communication make them emotionally better. There are three imporant positions of familiy in developing a child’s communication. First, parents can increase the capacities and capabilities in semantics, syntactics and pragmatics. These are linguistic dimensions that underlie child’s communication capabilities. Second, parents can be referent for a child in seeking social involvements and social needs. These dimensions can be seen in two forms of interaction: involvement and dependency. Third, parents can be model for a child. For manifestation and involvement in the social interaction, a child imitates and depends on the parents to express his/her emotion. The research concludes that family has important role in enhancing the development of linguistic and communication competence in infant.